Implementing a Diversity-Orientated Online Graduate-Level Health Professions Education Program | Soutenir la mise en place d'un programme de maîtrise en pédagogie universitaire des sciences de la santé offert à distance par et pour la diversité - Isabelle Savard (The Canadian Network for Innovation in Education (CNIE), 2015)
This case describes the strategies implemented in the development of an online Master's degree program in Health Professions Education (HPE) and an online short, Master's level diploma program. The strategies presented pertain to three of the main challenges identified: program cohesiveness, a multidisciplinary approach, and information technology literacy. The case describes meetings between the senior instructional designer, the program director, and the members of the development committee, which occurred over a period of approximately one year.